PIVKA-II but not dp-ucMGP is associated with aortic calcification in chronic kidney disease - Jakob Nyvad; Kent Lodberg Christensen; Gratien Andersen; Mark Reinhard; Bjarne Linde Nørgaard; Jonna Skov Madsen; Sebastian Nielsen; Martin Bjergskov Thomsen; Jesper Møller Jensen; Christian Daugaard Peters; Niels Henrik Buus (BMC Nephrology)
Abstract Background Patients with chronic kidney disease (CKD) are susceptible to vascular calcification and vitamin K deficiency. Matrix gla protein (MGP) is a potent inhibitor of calcification requiring vitamin K for activation. Inactive MGP, i.e. dephosphorylated uncarboxylated MGP (dp-ucMGP), is frequently elevated in CKD along with protein induced by vitamin K absence (PIVKA-II). We investigated whether dp-ucMGP and PIVKA-II are useful markers of aortic calcification in CKD. Methods Patients with normal or reduced kidney function underwent a non-contrast computed tomography scan of the entire aorta with subsequent blinded standard calcification scoring of the aortic wall ad modum Agatston. Blood samples were analyzed for plasma concentrations of dp-ucMGP and PIVKA-II. Results 141 patients (104 with CKD stage 3–5) were included. In patients with/without CKD median (interquartile range) were dp-ucMGP 543 (503–744)/1078 (835–1682) pmol/l (P < 0.01); PIVKA-II 19.3 (16.3–23.5)/21.8 (17.2–36.8) ng/ml (P = 0.33) and aortic Agatston scores 1644 (729–4138)/7172 (2834–15360) (P < 0.01). Agatston score was positively associated with PIVKA-II (β = 0.71, P = 0.014, r2 = 0.04) and tended to be so with dp-ucMGP (β = 0.44, P = 0.08, r2 = 0.02). Age, estimated glomerular filtration rate (eGFR) and smoking status were also associated with Agatston score and remained so, along with PIVKA-II, when adjusted for potential confounders. However, the association between age and aortic Agatston score was stronger than for PIVKA-II, eGFR and smoking-status. Conclusion Vitamin K deficiency, as estimated through PIVKA-II, but not dp-ucMGP, is weakly associated with aortic Agatston score. Yet, as markers of aortic calcification, both were outperformed substantially by age, and neither surpassed smoking nor eGFR. ClinicalTrials.gov identifier NCT04114695.